2019
DOI: 10.17521/cjpe.2019.0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term vegetation cover changes on the organic carbon fractions in soil aggregates of mollisols

Abstract: Aims Soil aggregate is the main habitat for decomposition and transformation of soil organic carbon (SOC) and is important to regulate SOC sequestration. The mechanisms of the stability of SOC fractions may vary among different aggregate sizes. The aims of this study were to explore the characteristics of SOC "fractionation" in soil aggregates, and to reveal the mechanisms of carbon (C) sequestration in soil aggregates of mollisols after 31-year changes in vegetation cover. Methods A long-term field experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Likewise, conservation tillage had a significantly larger MWD and GMD and exhibited more M of water‐stable aggregates than traditional tillage practices (Y. Li et al., 2019). No‐tillage plus straw returning increased MWD and GMD of soil aggregates, decreased D, and increased the content of M. Additionally, both showed that no‐tillage and straw returning has significant effects on improving the stability of soil aggregates (Cai et al., 2011) and previous studies reported that SOC is correlated with the number of water‐stable aggregates (N. Li et al., 2019), SOC was significantly positively correlated with GMD ( R 2 = 0.31) (Wang, Qi et al., 2019). Also, there was a linear relationship between SOC and MWD ( R 2 = 0.93) (Ali, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Likewise, conservation tillage had a significantly larger MWD and GMD and exhibited more M of water‐stable aggregates than traditional tillage practices (Y. Li et al., 2019). No‐tillage plus straw returning increased MWD and GMD of soil aggregates, decreased D, and increased the content of M. Additionally, both showed that no‐tillage and straw returning has significant effects on improving the stability of soil aggregates (Cai et al., 2011) and previous studies reported that SOC is correlated with the number of water‐stable aggregates (N. Li et al., 2019), SOC was significantly positively correlated with GMD ( R 2 = 0.31) (Wang, Qi et al., 2019). Also, there was a linear relationship between SOC and MWD ( R 2 = 0.93) (Ali, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…The decreased SOC and TN are probably due to deforestation that destroyed soil structure (i.e., aggregation) leading to releasing the previously protected organic matter (Jiang et al, 2005;Xiao et al, 2009) and reduced terrestrial litter inputs (Xie et al, 2004;Luo et al, 2009). On the other hand, the changed vegetation types may influence soil moisture and temperature conditions and thus accelerate SOM decomposition (Luo et al, 2009;Fei et al, 2015). Besides, because of the fragile land scape and soil properties in the Karst areas, deforestation may greatly aggravate soil erosion, resulting in massive loss of soil nutrients (e.g., C, N).…”
Section: Response Ratio Of Soc and Tn Storage Due To Deforestationmentioning
confidence: 99%
“…On the contrary, shifting from cropland to perennial vegetation was reported to increase SOC accumulation by transforming more atmospheric C into the soil and simultaneously decrease C loss from decomposition and erosion (Post and Kwon, 2000;Guo and Gifford, 2002;Berthrong et al, 2009;Laganiere et al, 2010;Duan et al, 2018;Nave et al, 2018). As another key factor in maintaining soil quality, total nitrogen (TN) and SOC generally exhibit similar responses to LUCCs by changing the microbial conditions and litter inputs in ecosystems (Xie et al, 2004;Luo et al, 2009;Xu et al, 2019), hydrothermal conditions at the land surface (Luo et al, 2009;Jerome et al, 2010;Fei et al, 2015) and plant species (Nie et al, 2014;Pan et al, 2015), which, if considering the impact of human activities (Xiao et al, 2009;Deng and Shangguan, 2017), jointly determined the changes in TN storage. Thus, appropriate land-use management practices (e.g., reforestation and land restoration) have been considered as one of the major strategies for mitigating climate change (Richard et al, 2006;Song et al, 2014;Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%